EXPERIMENTAL AND NUMERICAL COMPARISON OF THERMODYNAMIC PERFORMANCES OF NEW AND OLD GENERATION REFRIGERANTS IN THE SAME COOLING SYSTEM - Das, Mehmet; Pektezel, Oguzhan (Vinca Inst Nuclear Sci, 2022)
The use of new generation low GWP refrigerants in cooling systems is becoming increasingly common due to thermal performance and less environmental impact. In this study, the thermal performance of the new generation R290 refrigerant and the old generation R404A refrigerant in the same cooling system were investigated experimentally and numerically. The thermal performance values of both gases were compared, provided that the temperature of the cold room cooled by the vapor compression cooling system drops to 0 degrees C. -5 degrees C, 0 degrees C, 5 degrees C evaporator temperatures and 25 degrees C, 30 degrees C, 35 degrees C condenser temperatures were used as operating parameters. The experimental results revealed that the highest COP values in the system for R290 and R404A were 4.68 and 3.94, respectively. An average of 9.38% increase in cooling capacity was detected with R290 compared to R404A refrigerant. In the numerical analysis part of the study, the evaporator surface temperature and air velocity distributions of both refrigerants in the cold room were shown numerically by using ANSYS FLUENT 19.1. As a result of the study, it was stated that R290 had higher thermal performance than R404A, according to both experimental and numerical analysis results.
Keywords: cold room; R290; thermal performance; COP; CFD analysis